Post appendectomy incisional hernia: a case report - Mishra, Abhishek; KC, Arjun; Harris, Matthew; Thapa, Samir (Journal of General Practice and Emergency Medicine of Nepal, 2022)
A 31-year-old man presented to the outpatient clinic at United Mission Hospital with colicky abdominal pain and bulge over the incision site which was more prominent on coughing. There was no fever. The abdomen was soft with no tenderness over the incision site and an expansive though reducible swelling was present over the right iliac fossa. The patient had undergone open appendectomy recently for acute appendicitis twenty days back. Ultrasonography revealed a 2.21cm muscle defect- findings consistent with interstitial incisional hernia. The patient underwent exploration through the same incision site electively. The subcutaneous tissue was found to be healthy. Anatomical repair with mesh placement was done. The postoperative period was uneventful and he was discharged on third postoperative day with instructions regarding dressing, removal of sutures on tenth postoperative day and avoidance of heavy weight lifting or straining and to follow up after a month.